2020
DOI: 10.1186/s13046-020-01730-8
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: SETDB1 promotes glioblastoma growth via CSF-1-dependent macrophage recruitment by activating the AKT/mTOR signaling pathway

Abstract: Background Glioblastoma is a common disease of the central nervous system (CNS), with high morbidity and mortality. In the infiltrate in the tumor microenvironment, tumor-associated macrophages (TAMs) are abundant, which are important factors in glioblastoma progression. However, the exact details of TAMs in glioblastoma progression have yet to be determined. Methods The clinical relevance of SET domain bifurcated 1 (SETDB1) was anal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…SET domain bifurcated 1 (SETDB1) is upregulated in GBM and promotes AKT/mTOR-dependent CSF-1 induction and secretion, which leads to macrophage recruitment in the tumor, resulting in tumor growth. Thus it is relative to poor progression [30].…”
Section: Gbm On Gamsmentioning
confidence: 99%
“…SET domain bifurcated 1 (SETDB1) is upregulated in GBM and promotes AKT/mTOR-dependent CSF-1 induction and secretion, which leads to macrophage recruitment in the tumor, resulting in tumor growth. Thus it is relative to poor progression [30].…”
Section: Gbm On Gamsmentioning
confidence: 99%
“…CSF1R, a type III protein tyrosine kinase receptor, is widely expressed by TAMs ( 70 ). The activation of CSF1R signaling by IL-34 or CSF1 induces the recruitment of macrophages and shifts the TAM phenotype from M1 to M2 ( 71 73 ). Pexidartinib (PLX3397), the first commercial CSF1R inhibitor approved by the Food and Drug Administration (FDA), was recently used in a phase II clinical trial of recurrent glioblastoma (NCT01349036).…”
Section: Tam-targeting Therapies For Gbmmentioning
confidence: 99%
“…Han et al. demonstrated that SETDB1 promoted AKT/mTOR-dependent CSF-1 induction and secretion, leading to macrophage recruitment in the tumor, and subsequently contributing to tumor growth ( 67 ). Additionally, De Boeck et al.…”
Section: Effects Of Glioblastoma On Tamsmentioning
confidence: 99%